PENGARUH PROPRIOCEPTIVE TRAINING TERHADAP NYERI OSTEOARTHRITIS LUTUT PADA LANJUT USIA (STUDI LITERATUR) - Wijayanti, Ni Wayan Devina; Bowo Laksono, Abdurrahman Berbudi; Sariana, Erna (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Background: Elderly is a term at the last stage of the aging process. Elderly people often experience health problems. This problem stems from the decline in body cells. Osteoarthritis (OA) is a degenerative and progressive joint disease associated with joint cartilage damage. This disease causes pain in sufferers which can interfere with daily activities and hinder functional tasks. Purpose: This study aims to identify the various literature related to the effect of proprioceptive training on knee osteoarthritis pain in the elderly. Research Methods: The study design used was a literature study. Data collection was carried out by downloading all literature that matched the inclusion and exclusion criteria with the publication time of the last 10 years. Literature was obtained from 4 search engines, namely PMC, Google Scholar, Pedro, and Semantic Scholar. Results: There were 10 literature relevant to 7 literatures using clinical trial study design and 3 literatures with RCT study design. The outcome obtained was pain with the measuring instruments used, namely VAS and NPRS. Overall, proprioceptive training has a significant change. Conclusion: proprioceptive training has an influence on knee osteoarthritis pain in the elderly from various literature. It is hoped that the public will know that proprioceptive training can be used to reduce knee OA pain